Particle-size distribution of channel bars of the lower Vistula between Bobrowniki and Bydgoszcz-Fordon (Geography and Tourism, 2017)
This study presents the diversity of sediments forming sand bars located in the Vistula channel between 695 km and 775 km of its course. The analysed section of the Vistula channel is located in the Toruń Basin. During the fieldwork carried out on 20-21 September 2011, 45 channel bars were identified and sampled. The collected samples were analysed in a laboratory. The obtained results were presented in the form of figures and graphics. The research related to the Vistula bed load performed to date was based on various research methods. The authors applied the sampling method used by Z. Babiński (1992). It was employed also by other authors (Habel, 2013). The obtained results were referred to other studies and the findings clearly indicate that such detailed research must be conducted along the whole middle section of the Lower Vistula valley.